Anticancer activities of franklinite ZnFe2O4nanoparticles made from Origanum vulgare leaf extract - Heba.Y.Jassim; Mustafa Hammadi (International Journal of Medical Toxicology and Legal Medicine, 2024)
In this study, a new, easy and cheap method was used to prepare ZnFe2O4 nanoparticles using Origanum vulgare leaf extract, where three methods were combined into one method: green chemistry, co-precipitation, and ultrasound to prepare ZnFe2O4 nanoparticles. The prepared nanoparticles were characterized using the following techniques: XRD, FT-IR, EDX, SEM, and DLS. The average size of the particles in the SEM was 134.48 nm, while the average size of the particles in the XRD was 41.88 nm. At the same time, the average size of the particles in the DLS was 381.5 nm. The effectiveness of the prepared ZnFe2O4 nanoparticles was compared with the drug Tamoxifen used in Iraq in treating breast cancer on the MCF-7 cell line. The results showed the excellent effectiveness of the prepared nanoparticles and their superiority over the drug used. They were also characterized by their lack of cytotoxicity compared to the toxicity of the drug on red blood cells in the toxicity screening test if the results showed cell killing for ZnFe2O4 (32.5%, 54.44%, and 76.7%. 89.37%, and 97.59%) while the drug Tamoxifen cell killing results are (8.01%, 17.14%, 28.96%, 43.56%.and 64.05%).